A Review of Privatization in Iran - Leila Sedighikamal; Ghodratollah Talebnia (International Journal of Management, Accounting and Economics, 2014)
Privatization has become a popular panacea for solving the organizational problems of governments by reducing the role of the state and encouraging the growth of the private sector enterprises. However, privatization takes a number of forms and has been approached in various ways during the move away from state control to other forms of ownership in developing and industrialized countries. Based on Iranian constitution, No.144, public companies must change to the private companies. The  government  of  Iran  urgently  needs  expanded and more dynamic private sectors, more efficient and effective  infrastructure/utility  provision,  and  increased investment  from  both  domestic  and  foreign  sources. The most important purpose of privatization in Iran is increasing the proficiency. In this article we will discuss about the reasons of this policy, forms and trends, privatization process and volume will be surveyed, article 44 and at the end performance of the government on privatization will be explained.